Inhibitory Effect of Selected Guaianolide and Germacranolide Sesquiterpene Lactones on Nitric Oxide Production - Harmatha, Juraj; Zídek, Zdeněk; Kmoníčková, Eva (Molecules (Basel, Switzerland), 2024)
Trilobolide and its analogues belong to the guaianolide type of sesquiterpene lactones, which are characteristic and widely distributed within the families Asteraceae and Apiaceae. Certain guaianolides are receiving continuously increasing attention for their promising sarco-endoplasmic reticulum Ca2+-ATPase (SERCA)-inhibitory activity. However, because of their alkylation capabilities, they are generally toxic. Therefore, the search for compounds with significant immunobiological properties but with decreased cytotoxicities suitable for use in immune-based pharmacotherapy is ongoing. Therefore, we extended our previous investigation of the immunobiological effects of trilobolide to a series of structurally related guaianolides and germacranolides. To evaluate the relationship, we tested a series of selected derivatives containing α-methyl lactone or exomethylene lactone ring. For a wider comparison, we also included some of their glycosidic derivatives. We assessed the in vitro immunobiological effects of the tested compounds on nitric oxide (NO) production, cytokine secretion, and prostaglandin E2 (PGE2) release by mouse peritoneal cells, activated primarily by lipopolysaccharide (LPS), and evaluated their viability. The inhibitory effects of the apparently most active substance, 8-deoxylactucin, seem to be the most promising.
Keywords: Sesquiterpenes, Guaiane; Animals; 8-epiisoamberboin; guaianolides; Cytokines; lipopolysacharidy; butyráty; germacranolides; Dinoprostone; cytokiny; Furans; Butyrates; dinoproston; Mice; Sesquiterpenes, Germacrane; seskviterpeny germakranové; Sesquiterpenes; Lipopolysaccharides; seskviterpeny; myši; laktony; furany; immune-modulatory effects; seskviterpeny guajanové; 8-deoxylactucin; peritoneální makrofágy; oxid dusnatý; zvířata; Lactones; Nitric Oxide; Macrophages, Peritoneal